The New Directive of the European Parliament and of the Council (EU) 2019/771 on Certain Aspects Concerning Contracts for the Sale of Goods: A Choice of Maximum Harmonization and Its Significance - Selvestravičiūtė, Agnė (Teisė, 2021)
This article examines the nature of maximum harmonization that underlies the Consumer Sales Directive, the goals of such choice, its practical implications, and argues that even though the level of consumer protection will not be radically changed due to the implementation of this directive, its adoption prompts legal instruments regarding consumer protection as tools for deeper market integration rather than solutions for fundamental problems which consumers face.